(untitled) (Zia e Tahqeeq, 2025)
The Islamic law of war sought to humanize armed conflict by protecting the lives of non-combatants, respecting the dignity of enemy combatants, and forbidding damage to an adversary’s property except when absolutely required by military necessity or when it happens unintentionally, as collateral damage. Prophet Muhammad (PBUH) led wars in His life and practiced these rules. War ethics like other body of law are derived from Qur’an and Sunnah which are ultimate sources of law in Islamic tradition. The basic idea working behind war laws in Islam is the protection of human life. This article describes war ethics in Islamic tradition particularly in the light of Seerat-un-Nabi and on other hand deals with international humanitarian laws regarding war. Studying the points of correspondence between Islamic law and modern international humanitarian law is not a matter of intellectual luxury; it is of strategic importance.